Bronchial hyperreactivity in sarcoidosis patients: correlation with airflow limitation indices - Martusewicz-Boros, M.M.; Boros, W.P.; Witar, et al., E. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Bronchial hyperreactivity (BHR) in sarcoidosis has been reported in 5 to 83% of patients, but the relationship between BHR and airway functional status being unclear. The aim of the study was to assess the prevalence and degree of BHR in a group of pulmonary sarcoidosis patients and how BHR does relate to the functional status of airways. Material and methods: 56 consecutive sarcoidosis outpatients (26 f, 30 m) were included. There were 14 (25%) patients in stage I, 32 (57.1%) patients in stage II and 10 (17.9%) patients in stage III. In all patients the standard evaluation included a history, physical examination, chest radiogram, serum ACE activity and lung function assessment were done. The provocation challenge test with doubling concentrations of histamine was performed in all patients using the standardized protocol recommended by the ERS. Results: 4 patients (7%) were restrictive, airway obstruction was detected in 7 (12.5%) cases. Up to 32% of patients had maximal expiratory flows at low lung volumes below the lower limit of normal (LLN). The histamine challenge test results: in 9 cases (16%) the fall in FEV1 was <20% of the baseline; mean PC20H (n=47) was 5.7 ± 5.9 mg/mL, range: 0.56-26.7 mg/mL. The challenge test was regarded as positive (PC20H≤8 mg/mL) in 71.4% of the group. BHR expressed as ln(PC20H) correlated weakly but significantly with FEV1, FEV1%VC, MMEF and PEF. Conclusion: BHR occurs frequently in sarcoidosis patients and should be considered especially in patients with airflow limitation.